Pengaruh Penggunaan Medial Arc Support Terhadap Tingkat Kelelahan Dan Stress Pada Penderita Fascitis Plantaris - Yopi Harwinanda Ardesa; Cica Tri Mandasari Ningsih; Muhammad Syaifuddin (Interest : Jurnal Ilmu Kesehatan, 2018)
Abstract: Plantaris Fascitis, Medial Arc Support, Fatigue, Stress. This research purpose to know the effect of Medial Arc Support in patients with plantar fascitis against fatigue and stress on employees packing PT TPS Food TBK. Experimental studies using quantitative methods to approach one group pretest-posttest design. The study population was all employees at PT TPS Food packing TBK suffering from plantar fascitis. To measure the reduction of pain in the plantar fasciitis with measuring tools such as Visual Analoc Scale by taking data on the day before treatment done and a day after the last treatment carried out (4 weeks). Examination carried out under pain painful motion, silent pain, and tenderness. Examination of pain before and after treatment. The results showed the average pretest fatigue patients with plantar fasciitis (24.60) while the average post-test (20.20). Wilcoxon test results showed statistical p value 0,000 <0,05 so that there is influence of Medial Arch Support to decrease fatigue in patients with plantar fasciitis. With the conclusion of the conclusions There is the influence of Medial Arch Support to decrease stress levels in patients with plantar fasciitis with p value 0,000 <0,05. There is the influence of Medial Arch Support to decrease fatigue in patients with plantar fasciitis with p value 0,000 <0,05.